Age-, Gender-, and in Vivo Different Doses of Isoproterenol Modify in Vitro Aortic Vasoreactivity and Circulating VCAM-1 - Nieto-Lima, Betzabé; Cano-Martínez, Agustina; Rubio-Ruiz, María E.; Pérez-Torres, Israel; Guarner-Lans, Verónica (Frontiers in Physiology, 2018)
Different human-like cardiomyopathies associated to β-adrenergic stimulation are experimentally modeled in animals through variations in dose, route, and duration of administration of different cardiotoxic drugs. However, associated changes in the vasculature and their relation to systemic inflammation, and the influence of cardiovascular diseases risk factors (gender and age) upon them are seldom analyzed. Here we studied the effect of age and gender on the vasoreactivity of aortas from mice subjected to in vivo repeated β-adrenergic stimulation with different doses of isoproterenol (ISO) in association with circulating inflammatory cytokines. Young (2 months) and old (18 months) male and female mice received 0 (control), 5, 40, 80 or 160 μg/g/d of ISO (7 days, s.c.). IL-1α, IL-4 and vascular cell adhesion molecule-1 (VCAM-1) were quantified in plasma. In vitro, norepinephrine-induced vasoconstriction and acetylcholine-induced relaxation were measured in aortas. No differences in contraction, relaxation, IL-1α, and IL-4 were found between control young males and females. Age decreased contraction in males and relaxation was lower in females and abolished in males. VCAM-1 was higher in young males than in females and increased in old mice. Vasoconstriction in ISO-treated mice results as a bell-shaped curve on contraction in young and old males, with lower values in the latter. In females, ISO-160 increased contraction in young females but decreased it in old females. Vasorelaxation was reduced in ISO-treated young males and females. ISO-80 and 160 reduced vasorelaxation in old females, and intermediate doses relaxed aortas from old males. VCAM-1 was higher in young and old males with ISO-80 and 160; while VCAM-1 was higher only with ISO-160 in old females. Our results demonstrate that repeated β-adrenergic stimulation modifies vascular reactivity depending on gender, age, and dose. Females were less sensitive to alterations in vasoreactivity, and young females required a higher amount of the adrenergic stimuli than old females to show vascular alterations. Changes were independent of IL-1α and IL-4. VCAM-1 only changed in old females stimulated with ISO 160. Our results highlight the relevance of considering and comparing in the same study females and aged organisms to improve the accuracy of applications to clinical studies.